Virtual Interviewing for Pediatric Emergency Medicine Fellowship—A National Survey. Issue 4 (5th April 2022) - van der Laan, Lyndsey; George, Rachel; Nesiama, Jo-Ann; Nagler, Joshua; Langhan, Melissa L.; Yen, Kenneth; Ngo, Thuy L.; Rose, Jerri A.; Caglar, Derya; Kant, Shruti; Ciener, Daisy; Feng, Sing-Yi
Abstract : Objective: This study aimed to evaluate both applicant and interviewer satisfaction with the virtual interviewing process for pediatric emergency medicine (PEM) fellowship in hopes to improve the fellowship interviewing process. It was proposed that fellowship programs and applicants would prefer virtual interviews over traditional interviews. Methods: A survey developed in collaboration with UT Southwestern PEM fellowship leaders and national PEM leaders was sent to all PEM fellowship applicants and programs at the conclusion of the 2020 interview season and rank list submission. The applicant survey obtained information on ease of virtual interviews and whether applicants felt that they obtained adequate information from virtual interviews to make informed program selections. Program director surveys collected data on thoughts and feelings about virtual interviews and obstacles encountered during the recruitment season. Both surveys asked about costs for interviews and interview type preference. Results: A response rate of 49% from applicants and 47% from programs was obtained. Virtual interview days were similar in the amount of time and staff hours used compared with traditional days. Applicants spent less on virtual interviews compared with those who underwent traditional interviews (average 725 vs 4312). Programs received more applications than the prior year and spent less money during the virtual cycle. The majority of the applicants (90%) were comfortable with the virtual interview platform, and most (66%) agreed that virtual interviews provided adequate information to determine program rank. Geography was the number 1 rank determining factor. Programs and applicants preferred a form of in-person interviews. Conclusions: Virtual interviews provide cost savings for both applicants and programs. Despite this, both parties prefer a form of in-person interviews.